The Reproducibility of the Jaw Index in the Measurement of Healthy Newborns. (May 2020) - Mermans, J.F.; Ghasemi, S.M.; Lissenberg-Witte, B.I.; Griot, J.P.W. Don
Objective: Establish the reliability of the jaw index to objectify the relationship between the maxilla and mandible in healthy newborns. Design: Cohort study. Setting: Tertiary setting. Patients: A total of 52 healthy newborns were included to detect an inter and intraclass correlation coefficient (ICC) of 0.8 with a 95% confidence interval (95% CI) of width 0.3. Inclusion criteria were children born full term without respiratory or feeding problems, and without congenital malformations or facial deformities due to birth trauma. Uncooperative patients were excluded. Interventions: The jaw index, a measuring tool for objectifying micrognathia in children suspected of having Robin sequence, was used. An ICC of greater than 0.8 was considered clinically relevant. Main Outcome Measure(s): Primary outcomes are the reliability of the jaw index expressed as interclass correlation coefficient and ICC. Secondary outcomes are the mean jaw index and mean length of the mandible, maxilla, and the alveolar overjet. Results: An interclass correlation coefficient of 0.74 (95% CI: 0.49-0.86) and an ICC of 0.81 (95% CI: 0.66-0.89) were found. The mandible had an average length of 162.6 mm (standard deviation [SD] 11.1), the maxilla 168.7 mm (SD 9.4), the alveolar overjet 2.0 mm (SD 0.60), and the mean jaw index was 2.1 (SD 0.64). Conclusion: The jaw index is a consistent instrument between different observers as well as for one observer measuring consecutively in the same child, to objectify the size of the lower jaw compared to that of the upper jaw in healthy newborns.